RICE GROWING IN THE AGRICULTURE OF TURKISTAN AND ITS CONDITION IN THE SECOND HALF OF THE XIX - BEGINNING OF THE XX CENTURIES (Scientific journal of the Fergana State University, 2023)
This article discusses the condition and cultivation of rice, which is one of the most important branches of agriculture in the Syrdarya, Samarkand and Fergana regions of the Turkestan in the second half of the 19th - early 20th centuries. The information on the specific experience and procedure of the locals in the cultivation of rice in the country, increasing the amount of arable land, supplying a water source, the amount of rice harvest, as well as its increase is presented in the article. Also, this article reveals measures against the cultivation of rice in the Turkestan territory of the colonial Russian Empire and the increase in such arable land.